2022
DOI: 10.1166/jon.2022.1894
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Magneto-Thermo-Bioconvection of Nanofluid Containing Gyrotactic Microorganisms Through Porous Media

Abstract: The present work aims to study the combined effect of external magnetic field and heating from below on the bioconvection of nanofluid containing gyrotactic microorganisms. Modified Maxwell’s equations and generalized Buongiorno’s model are used to frame the flow constitutive equations of nanofluid saturated in the Darcy-Brinkman porous medium. The present investigation has been done in the framework of linear stability. The resulting eigenvalue problem along with boundary conditions has been solved using Che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Throughout the study, the relative accepted error is set to 10 –6 , and graphical results are obtained for the momentum, thermal, and nanoparticle concentration profiles, as well as other physical quantities of engineering interest. The fixed values of the non-dimensional flow characterizing parameters [ (Bisht and Sharma, 2019; Sanjalee and Sharma, 2022; Sanjalee et al ., 2022a)? ] are chosen as follows: ξ = 0.3, κ = 0.3, Na = 5, Nb = 0.5, Le = 0.1, Da = 0.2, β * = 5, and Re = 10.The velocity profile in the absence of nanofluid and temperature are compared with the velocity profile obtained by Vajravelu and Kumar (2004) for K = 0, λ = 1, M = 1, and R = 0.1.…”
Section: Solution Methodologymentioning
confidence: 99%
“…Throughout the study, the relative accepted error is set to 10 –6 , and graphical results are obtained for the momentum, thermal, and nanoparticle concentration profiles, as well as other physical quantities of engineering interest. The fixed values of the non-dimensional flow characterizing parameters [ (Bisht and Sharma, 2019; Sanjalee and Sharma, 2022; Sanjalee et al ., 2022a)? ] are chosen as follows: ξ = 0.3, κ = 0.3, Na = 5, Nb = 0.5, Le = 0.1, Da = 0.2, β * = 5, and Re = 10.The velocity profile in the absence of nanofluid and temperature are compared with the velocity profile obtained by Vajravelu and Kumar (2004) for K = 0, λ = 1, M = 1, and R = 0.1.…”
Section: Solution Methodologymentioning
confidence: 99%
“…Kenjeres and Righolt [33] concluded that particle capturing efficiency in the targeted region increases due to magnetically targeted drug delivery. Sanjalee and Sharma [34] investigated the effect of the magnetic field on the onset of bioconvection due to gyrotactic microorganisms.…”
Section: Introductionmentioning
confidence: 99%